1998
DOI: 10.1074/jbc.273.38.24715
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Amyloidogenic Leu55→ Pro Transthyretin Variant Reveals a Possible Pathway for Transthyretin Polymerization into Amyloid Fibrils

Abstract: The x-ray crystal structure of the amyloidogenic Leu Based on the assumption that the observed packing contacts may be significant for amyloidogenesis, a model for the TTR amyloid is proposed. It consists of a tubular structure with inner and outer diameters approximately of 30 and 100 Å and four monomers per cross-section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 26 publications
(25 reference statements)
5
96
0
2
Order By: Relevance
“…X-ray diffraction studies of L55P TTR suggested this variant as an amyloidogenic intermediate in the process of TTR fibril formation. The mutation leads to the disruption of the D strand due to the disturbance of the hydrogen bonds between strands D and A, thus residues 54-56 are part of a long surface loop that connects strands C and E [27]. This variant, the less stable and most amyloidogenic among the tested ones, showed the lowest affinity to the peptide, whereas the anti-amyloidogenic one, T119M, showed the highest affinity, indicating that conformational molecular changes are important to the binding, and therefore, the D strand region is relevant in binding to A-Beta.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray diffraction studies of L55P TTR suggested this variant as an amyloidogenic intermediate in the process of TTR fibril formation. The mutation leads to the disruption of the D strand due to the disturbance of the hydrogen bonds between strands D and A, thus residues 54-56 are part of a long surface loop that connects strands C and E [27]. This variant, the less stable and most amyloidogenic among the tested ones, showed the lowest affinity to the peptide, whereas the anti-amyloidogenic one, T119M, showed the highest affinity, indicating that conformational molecular changes are important to the binding, and therefore, the D strand region is relevant in binding to A-Beta.…”
Section: Discussionmentioning
confidence: 99%
“…The first model was derived from TTRL55P representing a highly amyloidogenic variant showing an interesting packing within the crystal lattice, where specific monomers form a propagating chain involving associations within the loop regions (36). Through this arrangement a superhelix of selected monomers shows a fibril with the ␤-strands arranged parallel to the fibril axis.…”
Section: Discussionmentioning
confidence: 99%
“…Each TTR monomer contains eight strands that form two sheets of four strands each and are arranged in a topology similar to the classic Greek key barrel. However, TTR fibrils are not likely to be made up of the native tetrameric form, and transition may occur in which monomers are modified into a pathological conformation (Quintas et al, 1999;Sebastiã o et al, 1998). Bearing in mind other described ligands for RAGE (A␤, amylin, serum amyloid A, and prion protein) and the high ␤ sheet content of TTR, this seems to indicate that this receptor is prone to recognize ␤ sheet structures, which, in the case of TTR, might be present in both the soluble and fibrillar form.…”
Section: Sousa Et Almentioning
confidence: 99%